1981
DOI: 10.1111/j.1365-2265.1981.tb00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Control of Ketogenesis in Fasting

Abstract: The role of dopamine in starvation ketonaemia was investigated in male Wistar rats by administration of a specific dopamine receptor antagonist, metoclopramide (4 mg . kg-1 . 24h-1), or placebo, intragastrically during a 48-h fast. Starvation alone caused a fall in blood glucose and gluconeogenic precursor concentrations, which was unaffected by metoclopramide administration. Circulating 3-hydroxybutyrate and acetoacetate levels rose with fasting alone but metoclopramide impaired this ketonaemic response. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“… 34 Among them, a postsynaptic dopamine receptor antagonist could reduce ketonemia in a state of starvation. 35 Aripiprazole is an atypical antipsychotic with partial agonist activity at dopamine D 2 and serotonin 5 HT 1A receptors, as well as being antagonistic at 5-HT 2A receptors. 36 Changes in β-HB are primarily observed in the AZ group; however, this finding cannot be explained by the previous finding that dopamine antagonist reduces ketonemia, which may hint that neurotransmitter dopamine may be involved in the energy utilization process but cannot explain the entire mechanism.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Among them, a postsynaptic dopamine receptor antagonist could reduce ketonemia in a state of starvation. 35 Aripiprazole is an atypical antipsychotic with partial agonist activity at dopamine D 2 and serotonin 5 HT 1A receptors, as well as being antagonistic at 5-HT 2A receptors. 36 Changes in β-HB are primarily observed in the AZ group; however, this finding cannot be explained by the previous finding that dopamine antagonist reduces ketonemia, which may hint that neurotransmitter dopamine may be involved in the energy utilization process but cannot explain the entire mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently suggested that starvation might enhance peripheral dopaminergic activity as dopamine receptor blockade decreased the total ketone body levels in fasted rats (Belsa-Malpica et al, 1981). However, this may not apply to man or necessarily to all peripheral tissues in animals for the following reasons.…”
Section: Discussionmentioning
confidence: 99%